(untitled) - Feiferlikova, Romana; Mandysova, Daniela (Aura musica, 2021)
The article maps the latest additions to the choral works of Jan Vicar. Since 2020, the composer has composed three choral works for solo, choir and orchestra, which are waiting now their premiere and recording on CD. The cycles Shining Star and Five Carols for choir and orchestra are arrangements of well-known Czech and international carols, while the cantata Tereza's Stars is set to the lyrics by Jiri Zacek, Jan Vicar and folk poetry.
Keywords: Jan Vicar; choral compositions; 2020; 2021